Drain current model for undoped Gate Stack Double Gate (GSDG) MOSFETs including the hot-carrier degradation effects - Fayçal Djeffal; Toufik Bentrcia; M.A Abdi; T. Bendib (Microelectronics Reliability, 2011)
In this paper, analytical models of drain current and small signal parameters for undoped symmetric Gate Stack Double Gate (GSDG) MOSFETs including the interfacial hot-carrier degradation effects are presented. The models are used to study the device behavior with the interfacial traps densities. The proposed model has been implemented in the SPICE circuit simulator and the capabilities of the model have been explored by circuit simulation example. The developed approaches are verified and validated by the good agreement found with the 2D numerical simulations for wide range of device parameters and bias conditions. GSDG MOSFET design and the accurate proposed model can alleviate the critical problem and further improve the immunity of hot-carrier effects of DG MOSFET-based circuits after hot-carrier damage.